Hemodialysis‐related headache and how to prevent it. (11th October 2018) - Gozubatik‐Celik, G.; Uluduz, D.; Goksan, B.; Akkaya, N.; Sohtaoglu, M.; Uygunoglu, U.; Kircelli, F.; Sezen, A.; Saip, S.; Karaali Savrun, F.; Siva, A.
Abstract : Background and purpose: Hemodialysis (HD) may have some adverse effects on the nervous system. Headache is the most commonly reported neurological symptom amongst HD patients. Our aim was to determine the frequency, clinical characteristics and triggering factors of HD‐related headache (HRH) and to evaluate preventive strategies for reducing HRH. Method: In all, 494 patients were included. Comparative controls (CC) were classified within the same patients without headache. Arterial systolic/diastolic blood pressure, blood urea nitrogen (BUN) and creatinine were correlated before/after one HD. The urea reduction ratio during the dialysis session was determined. Results: A total of 175 patients (35.4%) with a mean age of 57.3 ± 15.7 years were diagnosed with HRH. HRH was more common in males ( P < 0.001). Headache was started a mean of 2.90 ± 0.86 h after the HD. The common localization of pain was reported to be bifrontal in 41.7% ( n = 73). The mean duration of headache was 6.22 ± 7.8 h, with a duration of ≤4 h reported by 64.0% of patients. The mean Visual Analog Scale score was 5.64 ± 2.05. The differences between pre/post‐dialysis BUN values were 94.6 ± 31.1 in HRH patients and 86.8 ± 28.5 in the CC group ( P = 0.006). The systolic blood pressure difference between the pre/post‐dialysis measurements was 22.4 ± 16.5 mmHg in HRH patients and 12.8 ± 19.4 mmHg in CC( P < 0.001). Patients with HRH had significantly higher mean systolic and diastolic blood pressure pre‐dialysis values (systolic, P = 0.002; diastolic, P < 0.001). The differences in systolic/diastolic blood pressure between pre/post‐dialysis were higher in the HRH group ( P < 0.001, P = 0.001, respectively). Conclusion: Regulating the frequency and timing of dialysis may provide better management in HRH with high BUN levels and high pre‐dialysis blood pressure.